Pola Komunikasi Kepemimpinan Kepala Desa dalam Upaya Pembinaan Generasi Muda Karang Taruna di Desa Serambi Kecamatan Jarai Kabupaten Lahat - Isnawijayani; Hazazi Hidayatullah, M. Daffa; Santhi Zinaida, Rahma; Misnawati, Desy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the communication pattern of village head leadership in efforts to foster the younger generation of coral cadets in Serambi Village, Jarai District, Lahat Regency. The theories used in this research are Behavioral Theory and ERG Motivation Theory. The research method used a descriptive qualitative approach, then the object of research was in Serambi Village, Jarai District, Lahat Regency. While the subjects of the study were village heads, community leaders, cadet reefs and the community. The result of this study is that there are three kinds of communication patterns of village heads in fostering the younger generation of coral cadets in Serambi Village, namely, personal communication, group communication, and mass communication. There are several ways that the village head has done to improve the moral development of the younger generation of coral cadets, namely: (1) Join the Karang Taruna Organization. (2) Weekly payroll. (3) Learning and being with the children of Serambi Village. (4) August 17 activities. (5) Mutual aid. (6) Eat together after the activity. (7) Sharing with others.